c-Myc Oncoprotein: A Dual Pathogenic Role in Neoplasia and Cardiovascular Diseases? - Napoli, Claudio (Nature Publishing Group, 2002)
A growing body of evidence indicates that c-Myc can play a pivotal role both in neoplasia and cardiovascular diseases. Indeed, alterations of the basal machinery of the cell and perturbations of c-Myc-dependent signaling network are involved in the pathogenesis of certain cardiovascular disorders. Down-regulation of c-Myc induced by intervention with antioxidants or by antisense technology may protect the integrity of the arterial wall as well as neoplastic tissues. Further intervention studies are necessary to investigate the effects of tissue-specific block of c-Myc overexpression in the development of cardiovascular diseases.